2013
DOI: 10.1108/ijmhsc-09-2013-0033
|View full text |Cite
|
Sign up to set email alerts
|

Assessment measures of Health-Related Quality of Life (HRQoL) of migrants: a systematic review

Abstract: Purpose -Definition-problems concerning the terms "migrant" and "Health-Related Quality of Life" (HRQoL) have a negative impact on the operationalization and measurement of the multidimensional and subjective construct of HRQoL. The aims of this systematic literature review are to address the following questions: How can the instruments used within the research field "migration and HRQoL" be described or categorized? Which dimensions (psychological, physical and social) and associated sub-dimensions have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…The WHOQOL-BREF, a shorter version of the WHOQOL-100, is a 26-item questionnaire developed by the WHO. The questionnaire was developed through field trials conducted in 14 countries using 12 different languages, making it cross-culturally valid and ideal for use in multicultural groups such as immigrant detainees ( 16 , 19 , 20 ). It is one of the most widely used tools for measuring QOL ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The WHOQOL-BREF, a shorter version of the WHOQOL-100, is a 26-item questionnaire developed by the WHO. The questionnaire was developed through field trials conducted in 14 countries using 12 different languages, making it cross-culturally valid and ideal for use in multicultural groups such as immigrant detainees ( 16 , 19 , 20 ). It is one of the most widely used tools for measuring QOL ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire was developed through field trials conducted in 14 countries using 12 different languages, making it cross-culturally valid and ideal for use in multicultural groups such as immigrant detainees ( 16 , 19 , 20 ). It is one of the most widely used tools for measuring QOL ( 19 ). The questionnaire contains 24 questions measuring QOL scores in four domains—environmental (eight questions), physical (seven questions), psychological (six questions), and social (three questions); in addition to two questions measuring general QOL and health ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this was the first study assessing HRQoL among elderly Turkish and Polish migrants and German natives [39]. The hypothesis was that being a migrant is associated with disadvantages that lead to a poorer HRQoL, expressed by Sf-36 sum scores, compared to natives.…”
Section: Discussionmentioning
confidence: 96%
“…However, only a few studies have focused on the health of migrants (Brussaard et al 2001). Buchcik et al (2013) reviewed 4,062 studies and revealed that only a few studies focused on the health-related quality of life (HRQOL) of migrants. But the health of migrants is at a disadvantage (Calderon et al 2012).…”
Section: Introductionmentioning
confidence: 99%